2020
DOI: 10.3389/fcell.2020.00236
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Adipose-Derived Stem Cells: The Cutting Edge of Clinical Application

Abstract: Adipose-derived stem cells (ASCs) represent a promising tool for soft tissue engineering as well as for clinical treatment of inflammatory and autoimmune pathologies. The well-characterized multi-differentiation potential and self-renewal properties of ASCs are coupled with their immunomodulatory ability in providing therapeutic efficacy. Yet, their impact in immune or inflammatory disorders might rely both on cell contactdependent mechanisms and paracrine effects, resulting in the release of various soluble f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 161 publications
(184 reference statements)
2
120
0
Order By: Relevance
“…It is known that MSCs secrete anti-inflammatory cytokines (IL-10, TGF-α, IDO, TSG-6, etc.) [15][16][17]31], and we have confirmed that MSC CellSaics secreted 3.1-fold more anti-inflammatory cytokine TSG-6 in response to concentration of inflammatory cytokine TNF-α than the MSC spheroids [20]. In reference [34], it is reported that transplantation of ALG-PLO microencapsulated islets trigger inflammation by increasing the TNF-α concentration at the transplantation site.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is known that MSCs secrete anti-inflammatory cytokines (IL-10, TGF-α, IDO, TSG-6, etc.) [15][16][17]31], and we have confirmed that MSC CellSaics secreted 3.1-fold more anti-inflammatory cytokine TSG-6 in response to concentration of inflammatory cytokine TNF-α than the MSC spheroids [20]. In reference [34], it is reported that transplantation of ALG-PLO microencapsulated islets trigger inflammation by increasing the TNF-α concentration at the transplantation site.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to spheroids, the spaces between the petaloid RCP pieces of the CellSaic allow for the sufficient penetration of substances into the cells, which effectively prevents cell death [13]. Mesenchymal stem cells (MSCs) are promising options as the cells comprising CellSaics for subcutaneous transplantation since they have revascularization, anti-inflammatory, and immunomodulatory abilities [14][15][16][17] and are known to enhance islet function when co-transplanted with them [18,19]. Our previous study demonstrated the continuous release of angiogenic factors and anti-inflammatory cytokines via a combination of MSCs and CellSaics (MSC CellSaics) [13,20].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest the possibility of developing a biobank of allogeneic MSCs for therapeutic purposes in several pathologies, since these cells lack the expression of class II MHC (Major Histocompatibility Complex) antigens and costimulatory molecules (CD80/B7.1 and CD86/B7.2) [ 39 ]. Noteworthily, the potential impact of donor-to-donor heterogeneity and the potential immunogenicity of allogeneic cells, depending on the culturing conditions and passages, the microenvironment, and the differentiation state, may alter the immunogenic phenotype, as recently reviewed [ 172 ].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Adipose tissue-derived stem cells (ASCs), a type of mesenchymal stem cell (MSC), possess significant anti-inflammatory and immunomodulatory properties that make them an attractive therapeutic option for numerous inflammatory diseases. ASCs exert their effects on the adaptive and innate immune system via the secretion of soluble molecules and extracellular vesicles (EVs), which alter the inflammatory microenvironment [ 1 , 2 , 3 , 4 ]. This is partially accomplished by transitioning activated macrophages from pro-inflammatory toward anti-inflammatory, pro-repair phenotypes [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%